![(x - 2)(x + 1) = (x - 1)(x + 3) (x - 2)(x + 1) = (x - 1)(x + 3)](https://tex.z-dn.net/?f=%28x+-+2%29%28x+%2B+1%29+%3D+%28x+-+1%29%28x+%2B+3%29+)
Answers
Answered by
1
Answer:
Given equation (x−2)(x+1)=(x−1)(x+3)
To find whether the given equation is a quadratic equation or not
Sol:
(x−2)(x+1)=(x−1)(x+3)
⟹x
2
+x−2x−2=x
2
+3x−x−3
⟹x
2
−x
2
+x−2x−3x+x−2+3=0
⟹−3x+1=0
This is not a quadratic equation as an equation of degree two is called a quadratic equation.
And, a polynomial when equated to zero or some value becomes an equation.
Answered by
0
__________________________
Fóllòw Më ❤
Similar questions
Computer Science,
3 months ago
India Languages,
3 months ago
Math,
3 months ago
English,
6 months ago